Macroalgae production in Northern Europe: Business and government perspectives on how to regulate a novel blue bioeconomy - Camarena-Gómez, María Teresa; Lähteenmäki-Uutela, Anu; Spilling, Kristian (Elsevier BV, 2022)
Highlights •Producers and authorities are key players developing the macroalgae sector in Europe. •Companies demand a specific macroalgae regulatory framework. •Authorities require assessment of the environmental risks of macroalgae production. •The license can be viewed as a boundary object between macroalgae companies and authorities. Abstract Macroalgae biomass production, understood as cultivation and harvesting, is a minor industry in Europe at present, but the sector is recognized as having substantial growth potential. Here, we framed the environmental license as a boundary object between business and authorities and investigated the details of macroalgal licensing procedures in seven Northern European countries (Finland, Estonia, Sweden, Germany, Norway, Iceland, and Scotland). We conducted surveys and interviews with macroalgae companies and licensing authorities to understand the challenges faced by both sides. Generally, macroalgae production in Northern European countries is regulated by environmental and water laws and is not included in maritime spatial plans. Private actors need to apply for an environmental, water and/or fishing permit to start operations in this sector, often with several authorities involved. The companies expressed their dissatisfaction with non-specific laws and burdensome licensing procedures that may delay or even prevent the start-up. The authorities highlighted the lack of scientific environmental risk assessments of macroalgae production and the need to resolve possible conflicts with other marine sectors. Companies need the license to access markets while authorities view the license as a tool to enforce environmental legislation. As a boundary object, the license is the result of correspondence and cooperation between companies and authorities. A one-step licensing procedure for macroalgae production should be applied to encourage this business and to facilitate the compliance of legislation. In addition, macroalgae related activities should be recognized in the ...